2023
DOI: 10.3390/genes14030742
|View full text |Cite
|
Sign up to set email alerts
|

Satellite DNAs—From Localized to Highly Dispersed Genome Components

Abstract: According to the established classical view, satellite DNAs are defined as abundant non-coding DNA sequences repeated in tandem that build long arrays located in heterochromatin. Advances in sequencing methodologies and development of specialized bioinformatics tools enabled defining a collection of all repetitive DNAs and satellite DNAs in a genome, the repeatome and the satellitome, respectively, as well as their reliable annotation on sequenced genomes. Supported by various non-model species included in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 197 publications
3
29
0
Order By: Relevance
“…The copyright holder for this preprint this version posted April 20, 2023. ; https://doi.org/10.1101/2023.04.18.537305 doi: bioRxiv preprint 2021; Iwata et al 2013;Shang et al 2010;Garrido-Ramos 2017;Šatović-Vukšić and Plohl 2023). In Alligatoridae, constitutive heterochromatin is restricted to the pericentromeric regions (Oliveira et al 2021) and includes the (peri)centromeric clusters found for the satDNAs isolated in this study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted April 20, 2023. ; https://doi.org/10.1101/2023.04.18.537305 doi: bioRxiv preprint 2021; Iwata et al 2013;Shang et al 2010;Garrido-Ramos 2017;Šatović-Vukšić and Plohl 2023). In Alligatoridae, constitutive heterochromatin is restricted to the pericentromeric regions (Oliveira et al 2021) and includes the (peri)centromeric clusters found for the satDNAs isolated in this study.…”
Section: Discussionmentioning
confidence: 76%
“…In general, a genome has a varied number of satDNA families (the satellitome, Ruiz-Ruano et al 2016) with varying nucleotide sequences and genomic abundance (Csink and Henikoff 1998;Kuhn et al 2008;Kuhn et al 2010;Plohl et al 2012;Feliciello et al 2015;Prakhongcheep et al 2017;Palacios-Gimenez et al 2017). Although some examples of small arrays scattered throughout euchromatin have been documented (Ruiz-Ruano et al 2016;Feliciello et al 2011Feliciello et al , 2015Kuhn et al 2012;Brajković et al 2012;Larracuente 2014;Pavlek et al 2015;Pita et al 2017;de Lima et al 2017;Robledillo et al 2020;Milani et al 2021), these sequences are often found in centromeres and in pericentromeric and subtelomeric heterochromatic areas (reviewed in Plohl et al 2012;Garrido-Ramos 2017;Šatović-Vukšić and Plohl 2023). More than just "junk DNA" (as for a long time considered) several studies have revealed that satDNAs have a role in a variety of biological processes, including gene regulation (Joshi and Meller 2017), centromere function (Rošić et al 2014), chromatin modulation (Ugarkovic 2005), and spatial chromosomal structure (Pathak et al 2013;Jagannathan et al 2018Jagannathan et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to consider that some of these satellites would be a component of the centromeric chromatin, much like in other species [ 4 , 5 ]. Although the presence of multiple dispersed loci composed of a single copy or a few tandem copies of a satDNA is a fact today [ 23 ], the accumulation of satDNAs (as well as other repetitive DNA families) in centromeres and in heterochromatic regions is characteristic, as observed in many other groups [ 4 , 23 , 85 87 ]. Such colocalization (i.e., the tendency to occupy similar locations on non-homologous chromosomes) might have been facilitated by the reunion of centromeres at the first meiotic prophase bouquet [ 6 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…2014; Ávila Robledillo et al . 2020; Šatović-Vukšić and Plohl 2023). Although the role of these repeats in centromere function has not yet been fully elucidated, several possible advantages of centromeric repeats have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In most plants, functional centromeres are epigenetically specified by the centromeric histone H3 variant (CENH3). CENH3 binding regions (hereafter CENH3 domains) in monocentric chromosomes are typically associated with extended arrays of tandemly repeated sequences (satellite DNA), which are usually highly divergent and fast evolving (Allshire and Karpen 2008;Plohl et al 2014;Ávila Robledillo et al 2020;Šatović-Vukšić and Plohl 2023).…”
Section: Introductionmentioning
confidence: 99%